Analisis Dampak Transformasi terhadap Kinerja Direktorat Corporate Banking PT Bank Mandiri (Persero), Tbk. - , Arizky Irwansyah ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Transformation of the company is a must for Bank Mandiri who wants to continue to exist and win the competition. The cause is that the banking business has high dynamics. Therefore the banking business world is not static, then the Bank Mandiri to be good at addressing the changes in the business world of banking. Entering the year 2005, the bank re-exposed to a variety of complex issues, such as high non-performing loans reached 25.2% or Rp 26.9 trillion, which causes a decrease in profit of Rp 5, 26 trillion in 2004 to Rp 0.6 trillion. The high level of NPLs, the resulting entry in the status of Bank Mandiri Bank in the Intensive Supervision of Bank Indonesia, thus limiting the space for Bank Mandiri in developing its business and reduce stakeholder confidence to Bank Mandiri. Looking at these developments, then in mid-2005 stakeholders took measures to change the composition of the management of Bank Mandiri to immediately take the necessary steps to restore the performance of Bank Mandiri as before but it is also fundamentally transforming the process of change in all aspects of the organization that Bank Mandiri can get out of the problems faced. SBU Corporate Banking as one business unit which operates in the corporate segment of customers are large companies of national and international scale are expected to have performance as expected from this transformation process. To find out the performance as expected it is necessary to evaluate the performance of the Financial Directorate of Corporate Banking during and after the process of transformation of PT Bank Mandiri (Persero), Inc. through an analysis that compares the performance between the realization of the targets and the use of financial ratios of the composition of assets and liabilities, the composition productivity / efficiency, a component of income. In this study, should see a financial impact during and after the transformation of PT Bank Mandiri (Persero) Tbk financial performance of the Directorate of Corporate Banking 2006-201. Later studies also analyzed using SWOT Analysis to identification factors the company's internal strengths and weaknesses with external conditions (environment) which describes the suitability or the best balance to determine next steps.